Respostas cardiovasculares ao teste de estresse mental em policiais militares e suas relações com o índice de apneia e hipopneia - Queiroz, Lucas Fortes de (2021)
The activity of police officers (POs) exposes them to mental stress in a chronic way, contributing to a framework of high risk factors for cardiovascular health. One of the prevalent factors that negatively affects the profession is obstructive sleep apnea (OSA). However, the possible influence of the apnea-hypopnea index (AHI) on the cardiovascular responses to mental stress (TS) in POs is still unknown. Therefore, the aim of the present study was to evaluate the relationship between the AHI and cardiovascular responses during the mental stress test (Stroop Test – ST) in POs in the state of São Paulo. POs aged 25 to 60 years, male, from the administrative sector of the police were recruited. Stress questionnaires (Lipp's Stress Symptom Inventory - ISSL) were applied to characterize the sample. Anthropometric measurements were taken, polysomnography (PSG) and cardiovascular variables were assessed at rest and during the TS: systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR) and heart rate variability (HRV). As a result, it was observed that 80% of POs had OSA (AHI>5 events/hour), and 58% had an AHI≥15 events/hour (moderate to severe OSA). In addition, 53% have <85% desaturation in PSG. There were correlations between the AHI and the responses of SBP, DBP, HR and HRV during the mean and peak ST (p<0.05). In the comparison between the two groups of POs with and without OSA, there was no difference in the responses of SBP, DBP, FC and HRV during the TS (p>0.05). It is possible to conclude that the hemodynamic and autonomic responses to the mental stress test are related to the AHI in POs.